Hubungan Pemberian ASI Eksklusif dengan Status Gizi pada Bayi di Wilayah Kerja Puskesmas Kuta Cot Glie Kabupaten Aceh Besar - Kurniatun Kurniatun; Khaira Rizki; Muhammad Daud (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Exclusive breastfeeding ensures the optimal development of children's potential intelligence. Babies without complete exclusive breastfeeding are more vulnerable to malnutrition. They face risks of both under-nutrition and over-nutrition. This study aims to determine the correlation between exclusive breastfeeding and nutritional status among infants in Kuta Cot Glie Public Health Center, Aceh Besar. This research was an analytical study with a cross-sectional approach. The sample consisted of 74 infants aged 0-6 months, selected using a Total Sampling technique. The study was conducted from May 1st to 23rd, 2025. The data were analyzed using univariate and bivariate methods with the Chi-Square test. Of the total 74 respondents, 44 respondents (59.5%) had a normal nutritional status. Additionally, 43 respondents (58.1%) were exclusively breastfed. The Chi-Square test showed a p-value = 0.001 < 0.05. The findings indicate a correlation between exclusive breastfeeding and nutritional status in infants. This study suggests that mothers exclusively breastfeed their babies. Therefore, mothers should also increase their knowledge by seeking information from various sources, such as clinics and professionals. This can help them understand the benefits of exclusive breastfeeding and how to prevent malnutrition in infants.